The boy, the mole, the fox and the horse - Mackesy, Charlie (London : Ebury Press, 2019)
"A modern, illustrated fable for readers of all ages that explores life's universal lessons from beloved British illustrator Charlie Mackesy"--
Keywords: Animals -- Comic books, strips, etc; Conduct of life -- Comic books, strips, etc; Fables, English; Graphic novels